Orthodontic Rubber Band-Assisted Endoscopic Submucosal Dissection: An Efficient Method for Treating Superficial Colorectal Tumors - Linfu Zheng; Wen Wang; Dazhou Li; Junguo Chen; Longping Chen; Rong Wang; Chuanshen Jiang; Guanpo Zhang; Yaping Hou; Jin Zheng; Yang Bai (Gastroenterology Research and Practice)
Background. Colorectal endoscopic submucosal dissection (ESD) is a complex operation. Effective traction is crucial. We have successfully used an orthodontic rubber band (ORB) combined with the clip traction method to assist ESD (ORB-ESD). The aim of this retrospective study is to describe the method and to compare the efficacy and safety of ORB-ESD versus conventional ESD in the treatment of superficial colorectal tumors. Methods. We retrospectively analyzed the data of patients with superficial colorectal tumor (with diameter≥20 mm) who received either ORB-ESD (n=34) or conventional ESD (n=90) between January 2019 and September 2020. Propensity score matching (PSM) was used to match the clinical data of 31 pairs of patients in each group. Results. Operation time was significantly shorter for ORB-ESD than for conventional ESD (34.5 minutes vs. 56 minutes, P≤0.001). In the propensity-matched cohorts, the operation time remained significantly shorter in the ORB-ESD patients (35 minutes vs. 50 minutes, P=0.001). Postoperative adverse events, en bloc resection rate, and R0 resection rate were comparable between the two groups (P>0.05), both before and after propensity score matching. In the ORB subgroup analysis, the trainee and expert ESD operation times were similar (37 (26–53) vs. 33.5 (26–37) minutes, respectively; P=0.274). Conclusion. ORB-ESD appears to be an effective technique for ESD of colorectal cancer. Our findings need to be confirmed in large prospective multicenter studies.